Los sistemas productivos de artesanías de hojalatería y el comercio justo en Riobamba - Aguirre Armijos, Evelyn Paulette, Salazar Villafuerte, Mauro Sebastian (2024)
ABSTRACT: The main objective of this research study, entitled "Los Sistemas Productivos de Artesanías de Hojalatería y el Comercio Justo en Riobamba" was carried out through the use of various methodologies, such as field, descriptive and explanatory, all of which were appropriate for its development. During the course of the research, surveys were carried out in five tinsmith workshops in Riobamba. Once the responses were collected, we proceeded to carry out a statistical analysis with the objective of verifying the reliability of the alternative hypothesis (H1), which states that "The production systems of tinsmith crafts influence fair trade in Riobamba". At the conclusion of our research, it is revealed that the current situation of the tinsmithing production systems is in an advanced stage, close to its possible extinction. Currently, these systems are being replaced by substitute materials that can be purchased at a lower price. This phenomenon highlights the urgent need to improve the connection with customers and enrich the shopping experience. It is crucial to implement a production model considering the cultural and economic importance they have.